Total cholesterol/high-density lipoprotein cholesterol ratio is a candidate predictor of survival outcomes in patients with metastatic renal cell carcinoma - Oktay Halit Aktepe; Ozge Yetginoglu; Mehmet Sinan Akarca; Canberk Sencan; Ahmet Unal; Elif Atag; Huseyin Salih Semiz; Aziz Karaoglu; Mustafa Erman; Suayib Yalcin (Scientific Reports)
Abstract This study aimed to investigate the predictive value of serum lipid levels, total cholesterol (TC)/ high-density lipoprotein cholesterol (HDL-C) ratio (TC/HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides in metastatic renal cell carcinoma (mRCC) treated with targeted therapy, sunitinib or pazopanib. A total of 111 mRCC patients were enrolled in this study. The correlation of lipid parameters with progression-free survival (PFS) and overall survival (OS) was performed with the Kaplan-Meier method and univariate and multivariate Cox regression models. The median PFS and OS of all patients were 12.2 months and 38.6 months, respectively. Receiver operating characteristic analysis showed that TC/HDL-C levels of 3.8 and 4 were optimal cut-off values in predicting PFS and OS, respectively. Patients with a high TC/HDL-C ratio had worse PFS and OS times than those with a low ratio (8.7 months vs. 19.3, p < 0.001; 24 months vs. 74.7 months, p = 0.003, respectively). Univariate analyses showed that among serum lipids, only the TC/ HDL-C ratio was associated with PFS (HR: 2.30, p < 0.001) and OS (HR:2.26, p = 0.004). When adjusted for the number of covariates, TC/ HDL-C was determined as an independent variable for the PFS (HR: 2.31, p < 0.001) and the OS (HR: 2.46, p = 0.003), respectively. The present study shows that TC/HDL-C ratio assessed in serum could be an important determinant for survival outcomes of mRCC patients treated with targeted therapy.